2019
DOI: 10.12659/msm.913829
|View full text |Cite
|
Sign up to set email alerts
|

Wogonin Increases Cisplatin Sensitivity in Ovarian Cancer Cells Through Inhibition of the Phosphatidylinositol 3-Kinase (PI3K)/Akt Pathway

Abstract: Background Wogonin (5,7-dihydroxy-8-methoxyflavone), one of flavonoids isolated from the Scutellaria baicalensis, has been regarded as an anticancer candidate because of its maximal efficacy in cancer cells. This study aimed to explore the possible mechanism that wogonin uses to enhance the sensitivity of ovarian cancer cells to cisplatin chemotherapy. Material/Methods The growth inhibition rates of ovarian cancer cells SKOV3/DDP and C13* were assessed by Cell Counting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Inhibitors of this signaling pathway are candidate drugs for management of this malignancy ( 19 ). Inhibition of PI3K/AKT also enhances the sensitivity of ovarian cancer to cisplatin treatment ( 20 ). In addition, a previous study reported that IMPA2 is involved in the phosphatidylinositol signaling pathway ( 21 ), thus, whether IMPA2 was also involved in the phosphatidylinositol signaling pathway in EOC cancer was investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibitors of this signaling pathway are candidate drugs for management of this malignancy ( 19 ). Inhibition of PI3K/AKT also enhances the sensitivity of ovarian cancer to cisplatin treatment ( 20 ). In addition, a previous study reported that IMPA2 is involved in the phosphatidylinositol signaling pathway ( 21 ), thus, whether IMPA2 was also involved in the phosphatidylinositol signaling pathway in EOC cancer was investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, CAL-27 (CL-0265, Procell, Wuhan, China) and human oral epithelial cells (CP-H203, Procell) were selected for in vitro experiments. In a 37°C cell incubator (51032124, Thermo Fisher Scientific, USA) with 5% CO 2 , CAL-27 was cultured in CAL-27 cell-specific medium (CM-0265, Procell) and human oral epithelial cells in human oral epithelial cell complete medium (CM-h203, Procell), both for 24 h. The cultured CAL-27 cells were assigned to control group and chemotherapy group, among which, cisplatin (10 μ g/mL, 100 μ L) [ 13 ] and paclitaxel (8 μ g/mL, 100 μ L) [ 14 ] were added to the culture medium of chemotherapy group. Eventually, the two groups of cells were cultured in cell incubator for another 24 h.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, it was reported that WOG exerted its antitumor potential through ameliorating p53 expression while suppressing tumor growth and glucose transporter 1 (GLUT1) in both in vitro and in vivo ovarian cancer models (Yikai et al, 2018). Besides, this compound was also found to enhance cisplatin sensitivity via suppressing PI3K/Akt pathway (Xing et al, 2019a). Combinatorial treatment of WOG and oridonin showed synergistic cytotoxicity through upregulating p53 expression and downregulating Akt expression in ovarian cancer cells (Chen et al, 2011b).…”
Section: Effect Of Wog In Different Cancersmentioning
confidence: 99%